THE MASTERY ON THE KEY TENSE MATCHING METHOD TO IMPROVE THE STUDENTSâ€™ ABILITY IN CREATING ENGLISH SENTENCES AT CLASS X STUDENTS IN MAS NURUL FALAH AIRMOLEK, INHU, RIAU - Loly Novita; Muhammad Sabri (INOVISH JOURNAL, 2019)
Abstract: The purposes of the research are to (1) introduce the method ofÂ  â€œThe Tense Key Matchingâ€ which is used to create English sentences easily to the Class X students of MAS Nurul Falah, Airmolek, INHU, Riau, (2) find out if â€œThe Key Tense Matchingâ€ is usable to be applied in Class X of MAS Nurul Falah, Airmolek, INHU, Riau to help the students face difficulties in creating English sentences so that they can master the four language skills in the future, and (3) know if the effectiveness of â€œThe Key Tense Matchingâ€ to the studentsâ€™ability in creating English sentences will give the effect on their English learning outcomes or not. This is a quasi experimental research which uses the pre-test and post-test design. The sample consist of two group: experimental class (given treatment of the tense key matching method) and controlled class (taught through conventional method). The subject of the research is the Class X students of MAs Nurul Falah Airmolek. The data is gathered through the techinqes of observation, test, documentation, and interview. Ttest Â is used to analysed the data. The result of the test shows that the tense key matching method is more effective than he conventionalÂ  method when it is applied in teaching English grammar (t = 8.547 and p Ë‚ 0.000).